Burden of comorbidities and medication use in childbearing women with rheumatic diseases: a nationwide population-based study - Min Kyung Chung; Chan Hee Lee; Jin Su Park; Hyunsun Lim; Jisoo Lee (The Korean Journal of Internal Medicine, 2022)
Background/Aims We aimed to estimate the prevalence of comorbidities and medication use in Korean women with rheumatic diseases (RDs) during their childbearing years. Methods We included women aged 20 to 44 years with seropositive rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and ankylosing spondylitis (AS) (n = 41,547) and age-matched women without seropositive RA, SLE, and AS (n = 208,941) from the National Health Insurance Service-National Health Information Database (2009 to 2016). The prevalence of hypertension (HTN), hyperlipidemia (HLD), diabetes mellitus (DM), and cancer and the use of nonsteroidal anti-inflammatory drugs (NSAIDs), corticosteroids (CSs), and disease-modifying anti-rheumatic drugs (DMARDs) were estimated. Results Women of childbearing age with RDs were more likely to have at least one of the measured comorbidities than the controls (odds ratio [OR], 3.0; 95% confidence interval [CI], 2.9 to 3.1). The OR (95% CI) was 2.9 (2.8 to 3.0) for HTN, 2.8 (2.7 to 2.9) for HLD, 1.4 (1.4 to 1.5) for DM, and 1.3 (1.3 to 1.4) for cancer. The SLE group had the highest prevalence and odds of all four measured comorbidities. Almost all (97.9%) women of childbearing age with RDs were taking RD-related medications (NSAIDs, 81.6%; CSs, 77.8%; DMARDs, 87.3%). The RD group was 13.8 times more likely to take NSAIDs and 68.2 times more likely to take CSs than the controls. Use of NSAIDs was more prevalent in RA and AS than SLE, whereas use of CSs and DMARDs was more prevalent in RA and SLE than AS. Conclusions Korean women with RDs have a greater burden of comorbidities and medication use during their childbearing years than women without RDs of the same age.